Pre-Eclampsia and Intrauterine Growth Restriction (IUGR)Prevention– Is Enoxaparin an Effective Option - Saeed, Saira; Barkat, Shafia; Murtaza, Badar (Pakistan Armed Forces Medical Journal, 2022)
Objective: To determine the effectiveness of Enoxaparin in preventing pre-eclampsia and intrauterine growth restriction in women with the history of pre-eclampsia and IUGR in an earlier pregnancy. Study Design: Quasi-Experimental Study. Place and Duration of Study: Department of Obstetrics and Gynaecology, Pak Emirates Military Hospital, Rawalpindi Pakistan, from Mar to Sep 2019. Methodology: In this study, a total of 186 pregnant females of age 20-40 years with >6 ± 0 and <16 ± 0 weeks gestation were included. They were divided into two groups. In the study group, injection Enoxaparin 40 mg s/c OD was started from 6 weeks to 36 weeks of gestation along with Aspirin 75 mg OD. In the control group, only Aspirin 75mg OD was given. An antenatal check-up was performed, and patients were followed for liquor volume, fetal growth and doppler ultrasound. Study outcomes were noted in terms of pre-eclampsia and intrauterine growth restriction. Results: The majority of the patients 100 (53.76%), were between 20-30 years of age. The mean gravidity in the study group was 3.84 ± 1.20 and in the control group was 3.83 ± 1.22. In this study, pre-eclampsia was found in 6 (6.45%) patients in the Enoxaparin group and in 17 (18.28%) patients of control group (p-value 0.014). Intrauterine growth restriction was observed in 9 (9.68%) patients of Enoxaparin group and in 28 (30.11%) patients of control group (p-value 0.001). Conclusion: This study concluded that Enoxaparin effectively prevents pre-eclampsia and intrauterine growth restriction in patients with a previous history....